A UNIVERSAL SOLUTION FOR UNITS - INVARIANCE IN DATA ENVELOPMENT ANALYSIS - XU, Jin; ZERVOPOULOS, Panagiotis D.; QIAN, Zhenhua; CHENG, Gang (Theoretical and Practical Research in Economic Fields, 2012)
The directional distance function model is a generalization of the radial model in data envelopment analysis (DEA). The directional distance function model is appropriate for dealing with cases where undesirable outputs exist. However, it is not a units-invariant measure of efficiency, which limits its accuracy. In this paper, we develop a data normalization method for DEA, which is a universal solution for the problem of units-invariance in DEA. The efficiency scores remain unchanged when the original data are replaced with the normalized data in the existing units-invariant DEA models, including the radial and slack-based measure models, i.e., the data normalization method is compatible with the radial and slack-based measure models. Based on normalized data, a units-invariant efficiency measure for the directional distance function model is defined.